Pengaruh Jenis Ban dan Tekanan Angin terhadap Efisiensi Pengereman pada Kendaraan Isuzu TBR 54: Pengaruh Jenis Ban dan Tekanan Angin terhadap Efisiensi Pengereman pada Kendaraan Isuzu TBR 54 - Anis Prabandari; Joko Winarno; Mochamad Syamsiro (Universitas Sarjanawiyata Tamansiswa, 2025)
The braking system is a critical component in ensuring the safety of motor vehicles. Braking effectiveness is influenced by the condition of the braking components and supporting factors such as tire type and air pressure. Inappropriate selection of tires or incorrect air pressure can reduce tire grip on the road surface, leading to decreased braking efficiency. Based on this background, this study aims to analyze the effect of variations in tire type (bias and radial) and tire air pressure on the braking efficiency of the Isuzu TBR 54 vehicle. The research was conducted at the Motor Vehicle Testing Unit of the Department of Transportation in Magelang City using an experimental method. A Certus 2023 brake tester was employed to collect data. The variables tested included two types of tires and five different air pressure levels (25, 30, 32, 35, and 40 psi). Braking force data on both vehicle axles were collected and analyzed using SPSS software through normality tests, homogeneity tests, and t-tests to determine the significance of each variable’s influence. The results showed that tire type and air pressure significantly affect braking efficiency. Radial tires demonstrated better braking performance than bias tires across all pressure levels. Excessive air pressure reduced braking efficiency due to a decrease in the tire’s contact area with the road surface. The most optimal combination for braking efficiency is achieved with radial tires at an air pressure of 25–30 psi, which results in braking efficiency above 75%. These findings highlight the importance of selecting the appropriate tire type and maintaining proper air pressure to enhance vehicle safety and braking performance.